Virus envelope markers in mammalian tropism of avian RNA tumor viruses. - Boettiger, D (1975)
Pseudotypes of vesicular stomatitis virus were prepared with avian sarcoma viruses and avian leukemia viruses representing five different subgroups. These pseudotypes display a host range restricted to that of the avian tumor virus when assayed on avian cells and are neutralized by subgroup-specific antisera. The efficiency of penetration of mammalian cells was assayed by using these vesicular stomatitis virus pseudotypes. Pseudotypes of avian tumor viruses belonging to subgroup D and of B77 virus were able to plate on mammalian cells with a high efficiency, whereas pseudotypes of other strains were not. The efficiency of penetration of the vesicular stomatitis virus pseudotypes was 10-2-to 10-3-fold higher than the efficiency of transformation of the corresponding avian tumor virus strain assayed on mammalian cells, suggesting that there are postpenetration blocks to the expression of transformation in these cells.